Função Quadrática: uso de material concreto no cálculo de raízes - Brandão, Claudiane Cardoso (Brasil, 2024)
The present work deals with the resolution of the calculation of roots using concrete material focused on the resolution of the 2nd degree function. The proposed objectives were: to reflect on the teaching-learning process of the function of the 2nd grade in high school and to explore the calculation for solving this function with the use of the golden material. The use of this pedagogical tool comes from the possibility of expanding the student's reasoning in understanding what it is and how to solve them. The results obtained revealed that the use of concrete material, when well explored in the classroom, facilitates greater student participation and, consequently, promotes the understanding of the contents developed.